PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP PEMBELAJARAN MATEMATIKA SISWA DALAM MATERI KOORDINAT KARTESIUS DI KELAS VIII SMP N 2 AMURANG - Mononimbar, Eunike Jeylinda Richilya; Pitoy, Cori; Salajang, Santje M (SOSCIED, 2025)
This study aims to identify whether the learning outcomes of students who learn using the Numbered Head Together (NHT) learning model are higher than the learning outcomes of students who learn using the Conventional learning model on Cartesian Coordinates material. This research is a study that uses a posttest-only control group design. The population of this study were all students of class VIII and the samples in this study were class VIII A as an experimental class consisting of 30 students and class VIII B as a control class consisting of 30 students at SMP N 2 Amurang in the academic year 2024/2025. The results revealed that there were differences in the learning outcomes of students taught using the Numbered Head Together (NHT) learning model with students taught using the Conventional learning model. Based on the above results, it is concluded that learning by using the Numbered Head Together (NHT) learning model can improve students' mathematics learning outcomes on Cartesian Coordinates material.